2002
DOI: 10.1046/j.1537-2995.2002.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Volume of RBCs, 24‐ and 48‐hour posttransfusion survivals, and the lifespan of 51Cr and biotin‐X‐N‐hydroxysuccinimide (NHS)‐labeled autologous baboon RBCs: effect of the anticoagulant and blood pH on 51Cr and biotin‐X‐NHS elution in vivo

Abstract: The anticoagulant and the pH of the medium in which the RBCs were labeled with (51)Cr or biotin-X-NHS affected in vivo elution of the label from the RBCs and may reduce posttransfusion survival values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 27 publications
0
27
1
Order By: Relevance
“…Our recent observation in baboons transfused with autologous fresh RBCs labeled with 51 Cr and biotin‐X‐NHS demonstrated that the lesion of collection reported by Gibson and associates 32,33 was due to 51 Cr elution from the fresh RBCs and not to the removal of nonviable 51 Cr‐labeled autologous RBCs 23 . When the pH value of the medium in which the RBCs are labeled is 6.0 or lower, the rate of elution of 51 Cr from the RBCs is increased 23 . The elution of 51 Cr, 99m Tc, and 111 In‐oxine from autologous liquid preserved RBCs reported by Marcus and associates 12 may have been affected by the pH of the RBCs at the time of labeling.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Our recent observation in baboons transfused with autologous fresh RBCs labeled with 51 Cr and biotin‐X‐NHS demonstrated that the lesion of collection reported by Gibson and associates 32,33 was due to 51 Cr elution from the fresh RBCs and not to the removal of nonviable 51 Cr‐labeled autologous RBCs 23 . When the pH value of the medium in which the RBCs are labeled is 6.0 or lower, the rate of elution of 51 Cr from the RBCs is increased 23 . The elution of 51 Cr, 99m Tc, and 111 In‐oxine from autologous liquid preserved RBCs reported by Marcus and associates 12 may have been affected by the pH of the RBCs at the time of labeling.…”
Section: Discussionmentioning
confidence: 83%
“…Poorly preserved autologous RBCs are removed from the circulation during the mixing time and will not be detected with the extrapolated 51 Cr‐labeled RBC radioactivity during the immediate posttransfusion period 39 . The 51 Cr label elutes at a rapid rate during the 24‐ to 48‐hour posttransfusion period and during the life span when the RBCs are labeled with 51 Cr in a medium in which the pH value is 6.0 or lower 23 . The increased rate of 51 Cr elution will reduce the 51 Cr 24‐hour posttransfusion survival and life span of the autologous preserved RBCs 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations